2020
DOI: 10.2196/17851
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-Related Topics in an Online Forum for Caregivers of Individuals Living With Alzheimer Disease and Related Dementias: Qualitative Inquiry

Abstract: Background Diabetes and Alzheimer disease and related dementias (ADRD) are the seventh and sixth leading causes of death in the United States, respectively, and they coexist in many older adults. Caring for a loved one with both ADRD and diabetes is challenging and burdensome. Objective This study aims to explore diabetes-related topics… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
0
20
0
Order By: Relevance
“…People living with chronic conditions use social media to share information, garner social support, and raise awareness and advocate for themselves and others (Berry et al, 2017;Gabarron et al, 2015;Hemsley et al, 2015;Himelboim & Han, 2014;Tsuya et al, 2014). Consistent with this, an emerging body of research has focused on the social media posts of people living with dementia and their caregivers (Bachmann, 2020;Craig & Strivens, 2016;Du et al, 2020;Anderson et al, 2017;McLennon et al, 2021;Talbot et al, 2020a;. People living with dementia use social media platforms as a way to participate in activism, connect and share support, and disseminate information (Clare et al, 2008;Craig & Strivens, 2016;Lorenz et al, 2017;Rodriquez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…People living with chronic conditions use social media to share information, garner social support, and raise awareness and advocate for themselves and others (Berry et al, 2017;Gabarron et al, 2015;Hemsley et al, 2015;Himelboim & Han, 2014;Tsuya et al, 2014). Consistent with this, an emerging body of research has focused on the social media posts of people living with dementia and their caregivers (Bachmann, 2020;Craig & Strivens, 2016;Du et al, 2020;Anderson et al, 2017;McLennon et al, 2021;Talbot et al, 2020a;. People living with dementia use social media platforms as a way to participate in activism, connect and share support, and disseminate information (Clare et al, 2008;Craig & Strivens, 2016;Lorenz et al, 2017;Rodriquez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…ADRD caregivers have increasingly sought support and shared their experiences through various general-purpose online social platforms, such as Twitter (Berry, Lobban et al 2017), Facebook (Pagán-Ortiz, Cortés et al 2014, as well as online health communities like ALZConnected (Du, Paiva et al 2020). While it has been shown that participating in online communities has certain benefits (e.g., a reduction in depressive symptoms) (Wilkerson, Brady et al 2018), the collection of studies to date are limited in that they focused only on a single ADRD community, such as r/Alzheimers on Reddit (Wang, Zou et al 2021), which does not provide a complete picture of the challenges that ADRD caregivers confront.…”
Section: Introductionmentioning
confidence: 99%
“…There has been an increased creation of social media and online health communities to support those living with certain diseases [13]. Emerging studies have reported social media and online communities as promising approaches to promote CKD care through various ways such as for data collection and providing support.…”
Section: Introductionmentioning
confidence: 99%